The Role of Digital Marketing for Generation Z - Razak, Ismail (SEAN Institute, 2022)
Generation Z. Generation Z, as a group of consumers born between the mid-1990s and early 2010s, grew up in an era of very sophisticated digital technology. Therefore, a deep understanding of how digital marketing strategies can influence Generation Z consumer behavior is important for marketers and researchers. This research aims to identify and analyze the role of digital marketing in influencing product preferences and purchasing decisions among Generation Z. This research uses a qualitative approach with descriptive methods. The research results highlight that Generation Z, as consumers who have grown up in the digital era, shows a tendency to place high value on authentic, engaged and personalized experiences. A successful digital marketing strategy to reach this group involves utilizing creative, interactive, and relevant content that aligns with their values. Additionally, supporting social and environmental issues can be a key element in building a positive brand image in the eyes of Generation Z. The success of digital marketing also depends heavily on responsiveness to mobile device use, with optimization for a good mobile experience being essential in attracting and maintain their attention.